Indentation Plastometry of Welds. Issue 9 (13th February 2022) - Gu, Wenchen; Campbell, Jimmy; Tang, Yuanbo; Safaie, Hamed; Johnston, Richard; Gu, Yuchen; Pleydell-Pearce, Cameron; Burley, Max; Dean, James; Clyne, Trevor William
Abstract : This investigation concerns the application of the profilometry‐based indentation plastometry (PIP) methodology to obtain stress–strain relationships for material in the vicinity of fusion welds. These are produced by The Welding Institute (TWI), using submerged arc welding to join pairs of thick steel plates. The width of the welds varies from about 5 mm at the bottom to about 40–50 mm at the top. For one weld, the properties of parent and weld metal are similar, while for the other, the weld metal is significantly harder than the parent. Both weldments are shown to be approximately isotropic in terms of mechanical response, while there is a small degree of anisotropy in the parent metal (with the through‐thickness direction being slightly softer than the in‐plane directions). The PIP procedure has a high sensitivity for detecting such anisotropy. It is also shown that there is excellent agreement between stress–strain curves obtained using PIP and via conventional uniaxial testing (tensile and compressive). Finally, the PIP methodology is used to explore properties in the transition regime between weld and parent, with a lateral resolution of the order of 1–2 mm. This reveals variations on a scale that would be very difficult to examine using conventional testing. Abstract : Profilometry‐based indentation plastometry (PIP) is applied to samples cut from submerged arc welds, obtaining stress–strain curves from small regions (≈1 mm wide and 0.3 mm deep). This mapping has revealed variations across both parent and weldment, particularly close to the fusion boundary. These are correlated with microstructural effects.